ANALISIS PENGARUH GAYA HIDUP PRIA METROSEKSUAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION - Ony, Johan Gunady; Lina, Lina (Jurnal Keuangan dan Bisnis, 2020)
The purpose of this reseach is to analyze the effect of Metrosexual Life Style to purchase’s decision of fashion. The population on this research are all of metrosexual man. Sample in this research using purposive sampling method, there are 50 metrosexual man. Data in this research are collected by questioner and analyze with a qualitative and quantitative method. Mean of clothes (3.85) is the highest than belt (3.74) and wallet (3.39). The result of this research shown that Activity (X1), Interest (X2) and Opinion (X3) of metrosexual man, simultantly and partially influence the purchase’s decision of fashion.